The kinematics of table tennis racquet: differences between topspin strokes - Bankosz, Z.; Winiarski, S. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: Studies of shot kinematics in table tennis have not been sufficiently described in the literature. The assessment of the racquet trajectory, its speed and time characteristics makes it possible to emphasize on certain technical elements in the training process in order, for example, to increase strength, speed of rotation or speed of the shot while maintaining its accuracy. The aim of this work was to measure selected kinematic parameters of table tennis racquet during forehand and backhand topspin shots, while considering the differences between these strokes in table tennis.